The Skill Of Using Words In Sonnets - Faizullayeva Obidakhan Kholbekovna (Genius Publishing Group, 2024)
This article is devoted to the study of Rauf Parfi's skill in using words and the artisticaesthetic features of his poems, in which the specific aspects of the poet's poems, the content-essence, imagery, and the transfer of image tools are discussed. special emphasis is given to the expression through
Keywords: incomparable; through; content; imagery